Use of Saliva in Alternative to Serum Sampling to Monitor Biomarkers Modifications in Professional Soccer Players - Francavilla, Vincenzo Cristian; Vitale, Francesco; Ciaccio, Marcello; Bongiovanni, Tindaro; Marotta, Claudia; Caldarella, Rosalia; Todaro, Lorenzo; Zarcone, Maurizio; Muratore, Roberto; Bellia, Chiara; Francavilla, Giuseppe; Mazzucco, Walter (Frontiers in Physiology, 2018)
We aimed to investigate the correlation between serum and salivary concentrations of steroid hormones and IgA, and the variation in concentrations of these biomarkers, across a soccer competitive season in a sample of players playing for an Italian major League team. Thirty-five elite male soccer players were recruited and assessed for salivary hormones (cortisol, testosterone, T/C‰ and DHEA-S) and IgA at 3 different time-points: t1) after the pre-season period and 16 official matches played; t2) after a winter break and 2 official matches played; t3) two days after the final match of the championship and 19 matches played. Players were also tested for blood biomarkers (ser-C, ser-T, ser-T/C‰, ser-IgA, ACTH) at two detection times (t1 and t3). Blood samples were collected immediately after saliva sampling. The Spearman’s rank correlation was used to explore the correlation between blood and salivary concentrations of cortisol, free testosterone and IgA in the different time points. One-way ANOVA and permutation test were performed to explore changes by time of hormones and IgA concentrations over the competitive season. We documented a positive correlation between serum and saliva concentrations for Cortisol at t1 (+58.2%; p-value= 0.002) and t3 (+54.2%; p-value= 0.018) and for Testosterone at t1 (+42.0%; p-value= 0.033). Moreover, a positive variation was documented across the season (t3 – t1) for Cortisol (= +6.83; SEM= ± 2.70; Var%= +37.6; p-value= 0.032), Testosterone (= +0.33; SEM= ±0.07; Var%= +27.3; p-value= 0.002) and DHEA-S (= +44.48; SEM= ±18.54; Var%= +82.0; p-value= 0.042), while a decrease of sal-T/C ratio and no variation in salivary IgA concentrations were reported. In conclusion, our findings support for experimental use of saliva samples to monitor steroid hormones modifications in professional soccer players across a competitive season.